The Potential Usefulness of Magnetic Resonance Guided Focused Ultrasound for Obsessive Compulsive Disorders - Jung, Hyun Ho (J Korean Neurosurg Soc, 2018)
Obsessive compulsive disorder is a debilitating condition characterized by recurrent obsessive thoughts and compulsive reactions. A great portion of the obsessive compulsive disorder (OCD) patients are managed successfully with psychiatric treatment such as selective serotonin-reuptake inhibitor and cognitive behavioral psychotherapy, but more than 10% of patients are remained as non-responder who needs neurosurgical treatments. These patients are potential candidates for the neurosurgical management. There had been various kind of operation, lesioning such as leucotomy or cingulotomy or capsulotomy or limbic leucotomy, and with advent of stereotaxic approach and technical advances, deep brain stimulation was more chosen by neurosurgeon due to its characteristic of reversibility and adjustability. Gamma knife radiosurgery are also applied to make lesion targeting based on magnetic resonance (MR) imaging, but the complication of adverse radiation effect is not predictable. In the neurosurgical field, MR guided focused ultrasound has advantage of less invasiveness, real-time monitored procedure which is now growing to attempt to apply for various brain disorder. In this review, the neurosurgical treatment modalities for the treatment of OCD will be briefly reviewed and the current state of MR guided focused ultrasound for OCD will be suggested.